Bernegara ala Santri dalam Perspektif Maqashid Syariah Ibnu Asyur (Kajian atas Keputusan Munas Alim Ulama PBNU 2019) - Maimun, Ach. (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2023)
The strengthening of the Islamist movement and the assertion of the legitimacy of its conceptualization of the state, coupled with the accusation that modern state life represents a deviation from religious principles, gave rise to responses from a multitude of Islamic groups. At the National Conference of Alim Ulama of the PBNU in 2019, the santri highlighted the compatibility of their perspective with sharia on three key issues: the form of the nation state, the status of non-Muslims in the life of the nation and state, and the products of state laws and policies through modern mechanisms. This study focuses on determining the extent to which it aligns with the maqashid and the form of benefit that can be realized in accordance with sharia. This study employs a descriptive-analytical approach to examine the text of the 2019 National Conference of Alim Ulama PBNU decision, drawing upon Ibn Ashur's maqashid sharia theory. It can be concluded that the National Conference decision serves to protect the social order and preserve its goodness by relying on humans as al-maqshad al-'am. It enables the realization of maslahat and the rejection of mafsadat in the life of the nation and state as al-maqshad al-a'dzam of sharia. Secondly, the realization of maslahat as a maqashid sharia can be achieved through the pursuit of equality (musawah), justice ('adalah), freedom (hurriyyah), deliberation (syuro), and popular control (riqab al-ummah). This will facilitate the establishment of a harmonious, peaceful, and democratic society, thereby preventing the occurrence of mafsadat in the form of discrimination, inequality, oppression, and authoritarianism, which can give rise to disharmony, conflict, and chaos. The maslahat can be identified with clarity (wadhih) and is a pervasive phenomenon (ghalib), serving as a fundamental criterion for evaluating maslahat.